Penerapan Model Pembelajaran Collaborative Creativity (CC) Untuk Mengoptimalkan Keterampilan Berpikir Kritis (Critical Thinking) Pada Pembelajaran Matematika Di SMPN 2 Ranah Batahan Kabupaten Pasaman Barat - Fitri Suryani; Melisa Melisa; Hafizah Delyana (Universitas Katolik Widya Karya Malang, 2023)
The purpose of this study was to determine the effect of students' perceptions on the application of the Collaborative Creativity (CC) learning model to the mathematics learning outcomes of students in class X1 SMPN 2 Ranah Batahan Kabupaten Pasaman Barat. This research is motivated by low critical thinking skills students. The method in this research is pure experiment, with research design Noneequivalent posttest - only Control Group Design. The population in this study were students class IX SMPN 2 Ranah Batahan which consists of 3 classes. retrieval technique The sample used in this study is purposive sampling, so that The experimental class was selected, namely class IX 3 totaling 20. And the selected as the control class, namely class IX 2 totaling 20 students as research sample. The research instrument used is the final test. Test form used is an essay with test reliability is 0.901. Analysis technique The data used is the t-test. Based on the data analysis, it is obtained that tcount = 1.89 and ttable = 1.87, because tcount> ttable, then reject the Ho at a significant level of 0.05 so it can be concluded that the critical thinking skills of students who apply Collaborative Creativity (CC) learning model is better than students' critical thinking skills apply conventional learning.